POLA PEMARKAHAN ARGUMEN BAHASA KODI - Gusti Nyoman Ayu Sukerti; Yustinus Ghanggo Ate (Masyarakat Linguistik Indonesia, 2016)
This paper aims to describe the patterns of argument marking in Kodi, one of the local languages spoken in the area of Sumba, East Nusa Tenggara. The collected data were analyzed qualitatively using Role and Reference Grammar as the theoretical framework. As a typical head-marking language, Kodi language has extensive agreement or cross-referencing on heads such as verbs and nouns marked to agree with grammatical properties of their arguments including type and number of person. Kodi has pronominal clitics that mark morphological cases including nominative, accusative, genitive and dative. The overt subject and object, either in the form of pronominal or noun phrases, can be omitted and the sentence is still perfectly grammatical because the bound pronominal morpheme alone serves to indicate the function of predicate arguments. The overt subject and object are optional as they function to emphasize statements and to avoid ambiguity. S, A and O in Kodi are marked with different types of morphological cases. The predicate arguments can also be referred by clitic clusters, i.e., pronominal clitics with dative-dative and genitive-dative marking.